School based assessment and the comfort levels of secondary school teachers in Kuala Langat District when reporting issues and problems to the management - Sethupathy, Abel Raj; Zamri Ahmad, Professor Dr. Abdul Mua‟ti; Ghazali, Dr. Akmar Hayati; Yaakup, Dr. Hani Salwah (2018)
The purpose of this article is to observe the comfort levels of secondary school teachers in the district when reporting challenges faced in implementing the SBA to their respective school management. Besides, it also seeks to identify the reasons teachers provide for not communicating the challenges faced to the school authorities. The outcome of this study is beneficial to students, teachers, parents, the MOE and all stakeholders in the Education scenario in the country as it will indicate the success and direction of SBA as the standard curriculum across all national type schools in the district as well as the country.